Critical Discourse of President Jokowi's Speech on the Commemoration of World Anti-Corruption Day 2023 from Norman Fairclough's Perspective - Febriansyah Febriansyah; Hodairiyah Hodairiyah; Suhartatik Suhartatik (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to describe the use of diction, cohesion, and coherence in the text of President Jokowi's speech on the commemoration of World Anti-Corruption Day 2023 through the perspective of Norman Fairclough's Critical Discourse Analysis. Data collection was carried out using the Listen and Record technique. Then, the data was analyzed using the critical discourse analysis theory of the Norman Fairclough model which only focuses on the dimension of the text through the selection of diction, cohesion, and coherence in the speech text to understand the message about anti-corruption conveyed and its impact on public perception. The results of the analysis show that although the speech has a good structure and careful use of language, there are contradictions in the delivery that can cast doubt on the government's commitment to eradicating corruption. This study emphasizes the need for concrete actions that accompany speeches to achieve the goal of effective corruption eradication.